RIP140 deficiency enhances cardiac fuel metabolism and protects mice from heart failure - Tsunehisa Yamamoto; Santosh K. Maurya; Elizabeth Pruzinsky; Kirill Batmanov; Yang Xiao; Sarah M. Sulon; Tomoya Sakamoto; Yang Wang; Ling Lai; Kendra S. McDaid; Swapnil V. Shewale; Teresa C. Leone; et al. (The Journal of Clinical Investigation, 2023)
During the development of heart failure (HF), the capacity for cardiomyocyte (CM) fatty acid oxidation (FAO) and ATP production is progressively diminished, contributing to pathologic cardiac hypertrophy and contractile dysfunction. Receptor-interacting protein 140 (RIP140, encoded by Nrip1) has been shown to function as a transcriptional corepressor of oxidative metabolism. We found that mice with striated muscle deficiency of RIP140 (strNrip1–/–) exhibited increased expression of a broad array of genes involved in mitochondrial energy metabolism and contractile function in heart and skeletal muscle. strNrip1–/– mice were resistant to the development of pressure overload–induced cardiac hypertrophy, and CM-specific RIP140-deficient (csNrip1–/–) mice were protected against the development of HF caused by pressure overload combined with myocardial infarction. Genomic enhancers activated by RIP140 deficiency in CMs were enriched in binding motifs for transcriptional regulators of mitochondrial function (estrogen-related receptor) and cardiac contractile proteins (myocyte enhancer factor 2). Consistent with a role in the control of cardiac fatty acid oxidation, loss of RIP140 in heart resulted in augmented triacylglyceride turnover and fatty acid utilization. We conclude that RIP140 functions as a suppressor of a transcriptional regulatory network that controls cardiac fuel metabolism and contractile function, representing a potential therapeutic target for the treatment of HF.